CORPUS-INFORMED AND CRITICAL APPROACHES TO ADDRESSING SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Mambu, Joseph Ernest (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This paper showcases how a do-it-yourself (DIY) corpus on the United Nations’ Sustainable Development Goals (SDGs) can be used to increase corpus users’ language awareness (at word, phrase, sentence, and discourse levels) and criticality. To this end, the author justifies the close link between corpus linguistics, various critical approaches, and SDGs in the applied linguistics/ELT literature. Subsequently, the author provides an overview of principles for creating a specialized DIY corpus containing around 700,000 words/tokens based on 882 articles of The Jakarta Post from 2012 to mid-2024. In view of critical discourse analysis in corpus linguistics, SDG-related key word(s) in context (KWIC) were analyzed in four stages to examine their (1) frequencies and collocates, (2) concordance lines, (3) larger contexts within or across texts in the corpus (or beyond), and (4) potential to stimulate questions aiming at social transformation. In the findings, the four-stage analyses explore two of the most frequent SDGs in the corpus – “gender” (SDG 5) and “clean water and sanitation” (SDG 6) – to illustrate poststructuralist and Marxist criticality, respectively. The decolonial criticality is demonstrated through a corpus analysis of the word “indigenous” and its collocates. Possible pedagogical applications of the corpus-informed approach are also discussed.